BASE ON FINITE ELEMENT ANALYSIS OF PNEUMATIC PARACHUTE-PACKING MACHINE BODY OPTIMUM DESIGN - DENG SanPeng; WANG YingFei; QI Yu Ming; ZHOU WangFa (Jixie qiangdu)
A finite element analysis basing on transfer matrix method of multibody system for the parachute packing machine was finished in this article. After the research of multi-point cloud with the stress and displacement of the whole structure,considering the stress and deformation of the organization,the parachute packing machine has been optimized. It also has been verified by test that: the optimization has improved the working strength of the parachute packing machine,and the requirements of long time working at full capacity can be reached.